2021
DOI: 10.1002/jsfa.11214
|View full text |Cite
|
Sign up to set email alerts
|

Innovatively processed quinoa (Chenopodium quinoaWilld.) food: chemistry, structure and end‐use characteristics

Abstract: BACKGROUND: Quinoa (Chenopodium quinoa Willd.) flour and processed traditional Peruvian quinoa breakfast foods were studied to evaluate the effect of extrusion and post-processing on protein properties, morphology and nutritional characteristics (amino acids and dietary fibers). RESULTS:The extrusion increased quinoa protein crosslinking and aggregation observed by size exclusion high-performance liquid chromatography and the amount of soluble fibers, as well as decreasing the amounts of insoluble fibers in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…All of the extruded products made with the inclusion of pseudocereals showed a significant reduction in readily digestible carbohydrates and slowly digestible carbohydrates compared to the control product during predictive in vitro glycemic profiling. For quinoa it was shown that extrusion cooking increased protein crosslinking in quinoa and the amount of soluble fibre (Kuktaite et al, 2021). The content of essential amino acids was only reduced to a minor extent; only valine and methionine were reduced slightly greater, still the final product met the requirements of the Food and Drug Organization.…”
Section: Extrusion Cookingmentioning
confidence: 97%
See 1 more Smart Citation
“…All of the extruded products made with the inclusion of pseudocereals showed a significant reduction in readily digestible carbohydrates and slowly digestible carbohydrates compared to the control product during predictive in vitro glycemic profiling. For quinoa it was shown that extrusion cooking increased protein crosslinking in quinoa and the amount of soluble fibre (Kuktaite et al, 2021). The content of essential amino acids was only reduced to a minor extent; only valine and methionine were reduced slightly greater, still the final product met the requirements of the Food and Drug Organization.…”
Section: Extrusion Cookingmentioning
confidence: 97%
“…A strategy to foster starch gelatinization in quinoa might be pursued by adding higher amounts of water during extrusion cooking followed by subsequent drying of the extrudates. Kuktaite et al (2021) has shown that starch crystallinity decreased in particular during the postprocessing heating step.…”
Section: Extrusion Cookingmentioning
confidence: 99%
“…The quinoa ( Chenopodium quinoa Willd) plant is a pseudocereal highly consumed in South America since ancestral times by local people. Due to its high protein quality and mineral content, this crop has been widely cultivated in other continents, becoming a new producer [ 20 , 21 ]. As a result of industrial processing of the grain, tons of quinoa husk byproducts are obtained and must be disposed of in landfills.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some phytochemical constituents such as saponins, phenolic compounds (ferulic, sinapinic and gallic acids, kaempferol, isorhamnetin, and rutin) [4], and peptides with therapeutic activity have been determined, making this crop very attractive for a wide range of food products [5]. Quinoa has been traditionally used in tortillas, pasta, flour, cookies, bread, and soups, among others, and is considered to be a gluten-free superfood and a source of fiber dietary [6]. Thus, quinoa is considered to be an acceptable food worldwide and is highly recommended for vegetarians.…”
Section: Introductionmentioning
confidence: 99%